A Geopolitical Approach to the City ; with Emphasis on the Central Elements of Power and Competition - misanjas misanjas; Hasan Kamran Dastjerdi; Narjessadat Hosseini; Abbas Ghali Al-Hadithi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Many scholars believe that the city is a social innovation whose size , location , and internal organization are in terms of " power " ; And many changes in the structure and role - playing of the city are due to the mobility of " citizens " . The shape and appearance of the city , like the country , represents the pressure from the bottom up . Therefore , urban space processes have very low effects on the whole of politics , especially political development Competitiveness is one of the important issues that has been emphasized in urban literature in recent years and in this regard , different perspectives on the determinants of competitiveness have been presented . As a geographical phenomenon , the city has an effective role in power games and constitutes the most important spatial level of stress , action and competition in the present age . The present fundamental research with descriptive - analytical method express the fact that the necessary fields for their geopolitical study have been provided by creating a competitive environment and promoting the domestic and international competitiveness level of metropolises . Hence , an urban - scale geopolitics has made cities important actors in different geographical areas . The results of this study show that there is a relationship between the effectiveness of the roles of a place and the geographical area with its " power " . That is , as the roles have more extensive and in other words the broader function , the power of geographic location increases , like global cities . Indeed , the phenomenon of the city is studied and investigated in various dimensions , with emphasis on the central of politics , power and competition .    elements.